Risk of Depression in a Suburban Primary Care Setting Before and During the COVID-19 Pandemic - Carman H. Whiting; Pouran Yousefi; Jude K. A. des Bordes; Nahid J. Rianon (SAGE Publishing, 2023)
Introduction: Major depression is a common disorder affecting millions of adults each year. Many population-based surveys showed an increase in the number people with symptoms of depression at the onset of the COVID-19 pandemic. Our aim was to determine and compare the prevalence of depression risk in a primary care setting before and during the COVID-19 pandemic. Methods: We conducted a cross-sectional study based on retrospective review of medical records from a large suburban primary care clinic. Records of adults 18 years and older, seen between January 1, 2019 and December 31, 2020 and who had also been screened for depression using the 9-item Patient Health Questionnaire (PHQ-9) were analyzed. Results: Adults 18 years and older who completed the PHQ-9 assessment in 2019 and 2020 were 5078 and 4338, respectively. Risk of depression was 18.2% in 2019 and 14.8% in 2020 ( P  < .001). In adults under 50 years and those 50 years and older, depression risk was 20.7% versus 15.3% in 2019 ( P  < .001) and 17.3% versus 12.6% in 2020 ( P  < .001), respectively. In females, depression risk was 20.0% in 2019 and 16.8% in 2020 ( P  < .01), and in males, 14.1% in 2019 and 10.6% in 2020 ( P  < .01). Conclusion: Although our results did not reflect the published literature reporting a higher prevalence of depression during the COVID-19 pandemic, they were consistent with reports of increased risk in females and younger adults.